Aile konutu ve kira ilişkileri - Cumalı, Gamze (My University, 2012)
AİLE KONUTU VE KİRA İLİŞKİLERİ ÖZET Bu çalışmada Türk Medeni Kanunu ile Türk hukuk sistemine girmiş bulunan aile konutu ve aile konutunun kira sözleşmelerine etkisi ele alınmıştır. Çalışmanın birinci bölümünde aile konutu kavramının tanımı, unsurları ve koruma süresi izah edilmeye çalışılmıştır. Çalışmanın ikinci bölümünde ise Türk Medeni Kanunu ve Türk Borçlar Kanunu’nda aile konutu olarak kullanılan kiralanan ile ilgili özel hükümler incelenmiştir ve bu hükümlerin kira sözleşmelerine benzer sözleşmeler bakımından uygulanıp uygulanmayacağı sorusuna cevap aranmıştır. SINGLE FAMILY DWELLING AND LEASE RELATIONSHIPS

In this study, single family dwelling which has taken place in Turkish Law with Turkish Civil Code and single family dwelling’s effects about the lease relationship was discussed. In the first chapter of our study we tried to explain single family dwelling’s definition, elements and duration of protection. In the second chapter of the our study, we study the articles about single family dwelling and lease contracts which are taken place in Turkish Civil Code and Turkish Code of Obligations, and we look answer the question “if this articles can be applied about similar contracts”.
Keywords: Kira Sözleşmeleri; Özel Hukuk